Tiny encryption algorithm (TEA) for analysis and implementation of cryptool2-based text message encryption and decryption processes - Rohmah, Ahlam Umniyatur; Djuniadi, Djuniadi (SHM Publisher, 2023)
Data security is one of the main factors in the world of information technology. The human need for information is increasing along with the changing times today. To maintain the authenticity of the information presented, it is necessary to have a high level of security. In this study, a data security simulation will be designed using the TEA (Tiny Encryption Algorithm) algorithm which includes a block cipher encryption algorithm and includes a symmetric key cryptography algorithm with the advantage of being on the Feistel network. The practicum was analyzed based on the process of encrypting and decrypting messages in text format. The software used to simulate the TEA (Tiny Encryption Algorithm) algorithm using Cryptool2 software which is open source software is used to explain the concept of cryptography. This research is used to decipher, schema, and implement the TEA (Tiny Encryption Algorithm) algorithm in the form of simulating encryption and decryption of text messages (both text and text files) so that text messages are sent in the safest way from the sender to the recipient.